Public Examinations Examined - Kellaghan, Thomas (Washington, DC: World Bank, 2019)
This book addresses current issues related to the development, administration, scoring and usage of public examinations. High-stakes public examinations exert a dominant influence on education systems in Asia, Africa, Europe, Central Asia, the Middle East, and North Africa. They tend to have a major influence on teacher and student behavior, especially at the middle and upper levels of secondary education. The content of past examination papers tends to dictate what is taught and how it is taught and, more important, what is learned and how it is learned.